PHENOMENON OF MARKET ECONOMY IN REFLECTION OF PUBLIC CONSCIOUSNESS - Ya. S. Yadgarov; V. A. Sidorov; E. V. Sobolev (Финансы: теория и практика, 2017)
In thise article judgements of the modern Russian and foreign researchers are considered about the phenomenon of market economy and his refl ection in public consciousness. It is shown that introduction to the scientifi c turn it was not avouched for the classics of economic science of theoretical aspects of circulation of economic life the required stability of height of the labour, competitiveness, general effi ciency of public progress productivity. Attention applies, that, as well as before, researchers are not unanimous in the acceptance of sentence of untransient character of market economy, as and in the conditions of this type of management national and social priorities prevail not always, the problematic achievement of quality modernisation of productive forces and adequate reformation of productive relations is satisfi ed. The authors of the article solidarity with the conclusions, contained in those newest researches, according to that the modern comprehension of the phenomenon of market economy supposes providing of close collaboration of the state and large private structures, crossing and cooperation of their interests. Important is also a conclusion about the insistent necessity of creation in Russia of reliable institutional foundation of legal, economic and organizational infl uence of the state on the decision of vital problems, including a fi ght against corruption forms shadow (unmarket) economic relations.